Separation of Sub-Units of Antihemophilic Factor (AHF) by Agarose Gel Chromatography - Weiss, H. J; Phillips, Louise L.; Rosner, W. (Thrombosis and Haemostasis, 1972)
The molecular weight of antihemophilic factor (AHF) in plasma and cryoprecipitate was studied by chromatography on agarose gel (Bio-Gel A, 1.5 M). At a pH of 7.4 and the ionic strength of plasma, AHF appeared in the void volume as a sharp, symmetrical peak, indicating a molecular weight of 1.5 million or greater. Similar findings were obtained in a patient with congenital afibrinogenemia. At a pH of 7.7, the major peak of AHF-activity was again found in the void volume, but a spreading of activity into higher elution volumes was also observed. In 1 M NaCl, pH 7.4, AHF dissociated into active sub-units of varying molecular size. The molecular weights of the smallest subunits were estimated to be 169,000-194,000. These studies provide further evidence that AHF is a high molecular weight substance, not associated with fibrinogen, whose quarternary structure may be disrupted to produce active sub-units of varying sizes.